Binding of lactoferrin and free secretory component to enterotoxigenic Escherichia coli - Oliveira, Inaiara Rosa de (2001)
The ability of two glycoproteins of human milk, lactoferrin and free secretory component, to bind to Escherichia coli colonization factors (CFAs) was investigated using immunocytochemistry assays of enriched fimbrial extracts. The results revealed that lactoferrin binds to fimbrial CFA I adhesin but not to CFA II adhesin (CS1 and CS3), while free secretory component interacts with both CFA I and CFA II adhesins. Our data indicate that lactoferrin and free secretory component, which are very abundant proteins of human milk, could play an important role against infant enteric disease by blocking bacterial adhesion.